The Meaning of Moke for Ethnic Students of Sikka in the Era of Social and Technological Change: An Explorative Study From A Cultural Perspective - Ida, Gracia; Kiling, Indra Yohanes; Panis, Marleny Purnamasary; Syamruth, Yendris Krisno (Universitas Nusa Cendana, 2024)
The Sikka community has a rich cultural heritage, including the traditional Moke drink that enriches their ethnic identity. However, the influence of globalization, such as information technology, social media, international trade, and cultural exchange, has shifted the understanding and practices related to Moke from the previous generation to the younger generation. This study explores Sikka students' understanding and analysis of the moke tradition in the context of social and technological change. The research method used is qualitative, with semi-structured interviews in Kupang City, East Nusa Tenggara, involving Sikka ethnic students as subjects. The study results indicate that Moke is a drink and an important symbol in maintaining ethnic identity and traditional values. However, the challenges of preserving it in the modern era require adaptation to the dynamics of globalization without sacrificing the richness of this unique local culture.